Managers' sick-leave recommendations for employees with common mental disorders – a vignette study. (20th October 2021) - Hultqvist, J; Hensing, G; Stansfeld, S; Bertilsson, M
Abstract: Background: To better understand the initial phases of employee sickness absence due to common mental disorders (CMD), this study explores managers' recommendation for sick leave to a CMD-labelled video vignette case. The aim was to investigate the associations between sick leave recommendation and 1) managers' experience of persons with CMD, and 2) managers' previous recommendation of sick leave for employees with CMD, and 3) managers' attitudes toward employees with CMD. Methods: An online survey was sent in 2017 to 4, 737 Swedish managers, aged 20-65 years (71% participated, n = 3, 358). The survey included two randomized video vignettes, one female and one male. The vignettes were two minutes long. For aims 1 and 3 a study sample consisting of 2714 managers were used. For the second aim a sub-sample (n = 1740) was used due to the design of the survey questions. Results: The bi-variate analysis showed that personal experience of CMD was associated with managers' recommendation of employee sick leave. In the adjusted regression model, it became insignificant (p = 0.056). Having previous experience of recommending sick leave to one employee (OR 3.7, 95% C.I. 2.90-4.73), and to several employees (OR 7.1, 95% C.I. 4.27-11.82), were associated with recommending sick leave, adjusted for gender, level of education, years of managerial experience, and having had management training on CMDs. Finally, there was no significant association (p = 0.071) between negative attitudes towards employee depression and managers' recommendation of employee sick leave to the vignette case. Conclusions: The likelihood of a manager recommending sick leave after watching a CMD-labelled video vignette was higher if the manager had previously experienced this situation in real life. We consider this study being important as a first study looking into managers' attitudes and personal experience and recommendations of sick leave. Key messages: The odds for recommending sick leave to a video vignette case was higher if managers had this experience. This study highlights the importance of including managerial behaviors to understand the sick leave process for employees with CMD.